2005
DOI: 10.1007/11557654_11
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Traffic-Aware Routing (STAR) for Vehicular Systems

Abstract: Abstract-Vehicular ad hoc networks are studied with increasing interest for the many possible applications they have. Equipping vehicles with wireless devices primarily allows to design protocols and mechanisms to improve street safety. But also distributed applications for cooperative work, fleet management, passengers entertainment, could be supported. However, novel network protocols must be designed to make the deployment of vehicular networks possible.In this paper we consider the problem of data routing.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…For instance, empty or low vehicular density streets are avoided in packet forwarding as they are considered disconnected. In addition, forwarding a packet for a node which has no neighbours closer to destination can be eliminated by choosing roads with high density and good inter-vehicle communication quality [16]. Moreover, forwarding packets through congested routes can be prevented by considering data traffic load per street in routing decisions, which is called network status awareness.…”
Section: Traffic Aware Routing Concept and Classificationmentioning
confidence: 98%
“…For instance, empty or low vehicular density streets are avoided in packet forwarding as they are considered disconnected. In addition, forwarding a packet for a node which has no neighbours closer to destination can be eliminated by choosing roads with high density and good inter-vehicle communication quality [16]. Moreover, forwarding packets through congested routes can be prevented by considering data traffic load per street in routing decisions, which is called network status awareness.…”
Section: Traffic Aware Routing Concept and Classificationmentioning
confidence: 98%
“…Utilization of this information could be integrated into other protocols. STAR [26], CAR [49], and SADV [21] all explore slightly different methods for real-time traffic density detection. A careful study of these methods would be prudent, as areas for improvement may be found.…”
Section: Conclusion and Open Issuesmentioning
confidence: 99%
“…In designing the Spatial and Traffic Aware Routing (STAR) algorithm [26], the drawbacks of the SAR algorithm were observed. The SAR algorithm had the advantage of its underlying spatial model, allowing it to forward packets along streets.…”
Section: Spatial and Traffic Aware Routingmentioning
confidence: 99%
“…Forwarding from one AP to the next is performed using Geographic Forwarding. Spatial and TrafficAware Routing (STAR) [11] enhances SAR, allowing vehicles to collect and spread traffic information used to weight streets on the road map: the higher the vehicular traffic, the higher the score applied on a certain street. In Anchor-based Street and Traffic Aware Routing (A-STAR) [12], road map streets are weighted on the basis of known bus routes.…”
Section: Related Workmentioning
confidence: 99%